Consumer Global Orientation and Its Impact on Consumersâ Positive Emotions - Sulhaini, Sulhaini; Dayani, Rahman; Sulaimiah, Sulaimiah; Rusdan, Rusdan (Universitas Prasetiya Mulya, 2018)
The objective of this study is to examine the role of consumer global orientation and the inferior image of foreign brands in young, educated consumers admiration for foreign brands and willingness to pay more for foreign brands. As its sample, this study used students of the University of Mataram, with data collected in a classroom setting following the end of lectures using a carefully developed instrument that was carefully developed and tested through a stepwise procedure. Its findings suggest that consumer global orientation and the inferior image of local brands have no direct effect on consumers willingness to pay more for foreign brands. Nonetheless, they do indirectly affect consumer intentions by creating positive emotions about foreign brands. This positive emotion, i.e. foreign brand admiration, seems to have a critical role, as it fully mediates the effects of the two studied constructs. Consumer global orientation and the inferior image of local brands nurture consumers positive views of foreign brands, which in turn increase consumer willingness to pay higher prices for foreign brands. The paper also conceptualizes consumer global orientation and provides important managerial and recommendations for future research.Keywords:Â Consumer global orientation,Â inferior image of local brands,foreign brand admirationÂ https://doi.org/10.21632/irjbs.11.2.81-92